2019
DOI: 10.1002/adma.201807521
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembling Proteins as High‐Performance Substrates for Embryonic Stem Cell Self‐Renewal

Abstract: modeling of disease, drug discovery, the screening of toxicants, and personalized therapies in regenerative medicine for conditions like age-related macular degeneration and Parkinson's disease. [3,4] Human pluripotent stem cells (hPSCs), specifically human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs), are of critical significance in these pursuits. [5] Biomedical applications of hPSCs require large-scale ex vivo culture. Therapeutic uses require, in addition, xeno-free conditions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 40 publications
(90 reference statements)
1
20
0
Order By: Relevance
“…The crystal structures of RGD (Z 1212 RGD ; PDB: 6FWX) and KLER (Z 12 KLER ; PDB: 6SDB) modified variants as well as the NMR analysis of the FLAG single-domain variant (Z1 FLAG ) [39] confirmed that Z1 retained its native fold and structural integrity after the modifications and that the modified loop did not affect the long-range conformation of the Z 1212 tandem or its capability to polymerize through interaction with Tel. Furthermore, functional studies demonstrated that FLAG and SSGRGDSS sequences remained accessible and functional upon grafting, respectively supporting molecular and cell-based interactions with good efficiency [39,40]. These results established these Ig domains as successful scaffolds amenable to extensive protein engineering without detriment to their structural integrity, stability or assembly.…”
Section: Functionalization Of the Zt Polymer Using Genetic Engineementioning
confidence: 96%
See 4 more Smart Citations
“…The crystal structures of RGD (Z 1212 RGD ; PDB: 6FWX) and KLER (Z 12 KLER ; PDB: 6SDB) modified variants as well as the NMR analysis of the FLAG single-domain variant (Z1 FLAG ) [39] confirmed that Z1 retained its native fold and structural integrity after the modifications and that the modified loop did not affect the long-range conformation of the Z 1212 tandem or its capability to polymerize through interaction with Tel. Furthermore, functional studies demonstrated that FLAG and SSGRGDSS sequences remained accessible and functional upon grafting, respectively supporting molecular and cell-based interactions with good efficiency [39,40]. These results established these Ig domains as successful scaffolds amenable to extensive protein engineering without detriment to their structural integrity, stability or assembly.…”
Section: Functionalization Of the Zt Polymer Using Genetic Engineementioning
confidence: 96%
“…The display of peptidic sequences on the ZT polymer is established, with sequences having been introduced both in Tel and Z 1212 components without preventing polymerization [30,39,40]. Both components permit fusing peptidic sequences to their N- and C-termini and, in addition, Z 1212 permits the introduction of motifs in four internal positions, namely the CD loop of each of its four Ig domains (Figure 1b).…”
Section: Functionalization Of the Zt Polymer Using Genetic Engineementioning
confidence: 99%
See 3 more Smart Citations